A sufficient role of MHC class I molecules on hepatocytes in anti-plasmodial activity of CD8+ T cells in vivo - Huang, Jing; Tsao, Tiffany; Zhang, Min; Rai, Urvashi; Tsuji, Moriya; Li, Xiangming (Frontiers in Microbiology, 2015)
Although CD8+ T cells are shown to mediate the protective immunity against the liver stages of malaria parasites in mice, whether the direct presentation of malaria antigen by major histocompatibility complex (MHC) class I molecules expressed on the liver of infected host is required for anti-plasmodial activity of CD8+ T cells is still unknown. Presently, there is only one CD8+ epitope, SYVPSAEQI, derived from the circumsporozoite protein of Plasmodium yoelii (PyCS), that mediates anti-malarial protection and is presented in the context of a Kd molecule. Therefore, to investigate the mode of anti-plasmodial activity of CD8+ T cells, we have previously generated C57BL/6 transgenic (Tg) mice, in which a Kd molecule is expressed only on hepatocyte (Alb-Kd) or dendritic cell (DC) (CD11c-Kd), by using albumin promoter or CD11c promoter, respectively. We have also generated MHC-I-Kd Tg mice, which express the Kd molecule under the MHC class I (MHC-I) promoter, as a positive control. From splenocytes collected from CD11c-Kd Tg mice immunized with a synthetic peptide, SYVPSAEQI, which corresponds to the CD8+ T-cell epitope of PyCS, emulsified in incomplete Freund's adjuvant (IFA), a PyCS-specific CD8+ T-cell line was generated. This PyCS-specific CD8+T-cell line was then adoptively transferred into a cohort of either MHC-Kd Tg or Alb-Kd Tg mice listed above, as well as wild-type C57BL/6 mice. Then both transferred and non-transferred mice were challenged with live malaria parasites. We found that the adoptive transfer of a PyCS-specific CD8+ T-cell line resulted in a significant inhibition of the parasite burden in the liver of Alb-Kd Tg, as well as MHC-I-Kd Tg mice, but not of C57BL/6 mice. These results indicate that the Kd molecule expressed by hepatocytes is sufficient in mediating the anti-plasmodial activity of PyCS-specific CD8+ T cells in vivo.